Pharmacological Poly (ADP-Ribose) Polymerase Inhibitors Decrease Mycobacterium tuberculosis Survival in Human Macrophages - van Doorn, Cassandra L. R.; Steenbergen, Sanne A. M.; Walburg, Kimberley V.; Ottenhoff, Tom H. M. (Frontiers in Immunology, 2021)
Diabetes mellites (DM) is correlated with increased susceptibility to and disease progression of tuberculosis (TB), and strongly impairs effective global TB control measures. To better control the TB-DM co-epidemic, unravelling the bidirectional interactivity between DM-associated molecular processes and immune responses to Mycobacterium tuberculosis (Mtb) is urgently required. Since poly (ADP-ribose) polymerase (PARP) activation has been associated with DM and with Mtb infection in mouse models, we have investigated whether PARP inhibition by pharmacological compounds can interfere with host protection against Mtb in human macrophage subsets, the predominant target cell of Mtb. Pharmacological inhibition of PARP decreased intracellular Mtb and MDR-Mtb levels in human macrophages, identifying PARP as a potential target for host-directed therapy against Mtb. PARP inhibition was associated with modified chemokine secretion and upregulation of cell surface activation markers by human macrophages. Targeting LDH, a secondary target of the PARP inhibitor rucaparib, resulted in decreased intracellular Mtb, suggesting a metabolic role in rucaparib-induced control of Mtb. We conclude that pharmacological inhibition of PARP is a potential novel strategy in developing innovative host-directed therapies against intracellular bacterial infections.